Case Report: Two Cases of Metastatic Pancreatoblastoma in Adults: Efficacy of Folfirinox and Implication of the Wnt/β-Catenin Pathway in Genomic Analysis - Raoul, Jean-Luc; Oziel-Taieb, Sandrine; Lecomte, Thierry; Adelaide, José; Guille, Arnaud; Chaffanet, Max; Poizat, Flora; Heymann, Marie-Françoise; Barbier, Louise; Bertucci, François (Frontiers in Oncology, 2021)
Pancreatoblastomas are unfrequent tumors usually found in children. We report two cases of metastatic pancreatoblastomas observed in young women. A systemic chemotherapy (FOLFIRINOX regimen) was associated with a disease control in one case and a partial response in the second with an improvement of general status for both. A high-throughput sequencing of the tumor described in both cases alteration in the Wnt/β-catenin pathway: a mutation in CTNNB1 (exon 3, c.110C>G, p.S37C, reported as a hotspot in COSMIC) in one case and a homozygous loss associated with breakage targeting APC (5q22.2) in the second.